Clinicopathological features and impact of adjuvant chemotherapy on the long‐term survival of patients with multiple gastric cancers: a propensity score matching analysis. Issue 1 (11th February 2019) - Lin, Jian‐Xian; Wang, Zu‐Kai; Xie, Jian‐Wei; Wang, Jia‐Bin; Lu, Jun; Chen, Qi‐Yue; Cao, Long‐Long; Lin, Mi; Tu, Ru‐Hong; Huang, Ze‐Ning; Lin, Ju‐Li; Zheng, Chao‐Hui; et al.
Abstract: Background: Little is known about the correlation between the clinicopathological features, postoperative treatment, and prognosis of multiple gastric cancers (MGCs). In this study, we aimed to investigate the correlation between these features and the impact of postoperative adjuvant chemotherapy on the long‐term survival of patients with MGC. Methods: The clinical and pathological data of patients diagnosed with gastric adenocarcinoma who had radical gastrectomy from January 2007 to December 2016 were analyzed. Using propensity score matching, the prognostic differences, and the impact of postoperative adjuvant chemotherapy between those with MGC and solitary gastric cancers (SGC) were compared. Results: Among the 4107 patients investigated, the incidence of MGC was 3.2% (133/4107). Before matching, patients with MGC and SGC had disparities in the type of gastrectomy, pathological tumor stage (pT), pathological node stage (pN), and pathological tumor‐node‐metastasis stage (pTNM). After a 1:4 ratio matching, the clinical data of 133 cases of MGC and 532 cases of SGC were found to be comparable. The 5‐year overall survival (OS) rate was 56.6% in the entire matched cohort, 48.1% in the MGC group, and 58.7% in the SGC group ( P = 0.013). Multivariate analysis revealed that MGC, age, pT stage, pN stage, and adjuvant chemotherapy were independent predictors of OS (all P < 0.05). Stratified analyses demonstrated that for the cohort of advanced gastric cancer (AGC) patients who did not had adjuvant chemotherapy, the 5‐year OS rate of advanced cases of MGC was inferior than that of SGC patients (34.0% vs. 46.1%, respectively; P = 0.025) but there were no significant difference in the 5‐year OS rate between advanced MGC and SGC patients who had adjuvant chemotherapy (48.0% vs. 53.3%, respectively; P = 0.292). Further, we found that the 5‐year OS rate of advanced MGC who had adjuvant chemotherapy was significantly higher than those who did not had adjuvant chemotherapy (48.0% vs. 34.0%, P = 0.026). Conclusions: Patients with advanced MGC was identified as having a poorer survival as to SGC patients, but the implementation of postoperative adjuvant chemotherapy showed that it had the potential to significantly improve the long‐term prognoses of MGC patients.